Leachate valorization in anaerobic biosystems: Towards the realization of waste-to-energy concept via biohydrogen, biogas and bioelectrochemical processes. (28th June 2019) - Bakonyi, Péter; Dharmaraja, Jeyaprakash; Shobana, Sutha; Koók, László; Rózsenberszki, Tamás; Nemestóthy, Nándor; Banu J, Rajesh; Bélafi-Bakó, Katalin; Kumar, Gopalakrishnan
Abstract: Leachate generated in landfills is considered as a hazardous waste stream due to its composition and needs adequate treatment for environmental protection purposes. Nonetheless, a contemporary technology should not only be able to deal with its degradation, but at the same time, recover energy in various forms. Such valorization approaches with priority on these dual-aims are potentially those that rely on anaerobic biosystems. In the literature, processes considered on that matter include fermentative, digestive and bioelectrochemical set-ups to deliver energy-carriers such as biohydrogen (DF), biogas (AD) and electricity (BES), respectively. Moreover, to enhance the global efficiency of leachate utilization, it has been recently trending to develop integrated options by combining these systems (DF, AD, BES) into a cascade scheme. In this review, it is intended to give an insight to the research activities realized in these fields and show possible directions towards the better exploitation of leachate feedstock under anaerobic conditions. Highlights: Options for leachate valorization in anaerobic biosystems are overviewed. Treatment approaches with simultaneous energy recovery are outlined. Potential of biohydrogen, biogas and bioelectrochemical systems are discussed. Integrated applications are proposed for better process efficiency.